Outcome measurement in SLE patient: Indonesian version of RAND SF-36 summary scores and some scales were not reliable - Anggraini Kartika Sari Prita; Amelia Kharina; Cahyani Frameiza (BIO Web of Conferences)
Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease that can attack many organs with varying degrees of severity. This can affect quality of life (QOL). SF36 is a commonly used QOL test. This study aims to report the validity and reliability test of the Indonesian Version of RAND SF-36 in SLE patients. This research uses a cross sectional method and tested it on 19 eligible respondents. To test the reliability and validity of the questionnaire, analysis of the Cronbach coefficient and Pearson correlation was carried out. All subjects were women with an average age of 22.37 ± 5.10 years, the majority had secondary education (66.7%), were not married (79.2%), had no comorbidities (31.6%), and the duration of SLE was more than 3 years (62.5%). All of them used steroids as SLE therapy and also Mycophenolate mofetil (68.8%). The total value of Cronbach's alpha is 0.723 > 0.7, only two items were deemed appropriate RE scale (0.778) and GH scale (0.724). The validity sig value is < 0.005. In general, this study provides evidence that the Indonesian version of the RAND-SF 36 can be used to assess the QOL of SLE patients. However, there are limitations to the reliability of the scales. Further research or adjustments to the questions in the Indonesian version are required to enhance the reliability of the assessment.